Detection and diversity pattern of amaranth Cultivars originated in diverse region of Indian subcontinent - M. PARVEEN; S. RAY; N.C.CHATTERJEE (International Journal of Pharma and Bio Sciences, 2018)
Amaranths are most attractive and economic group of important plant as leafy vegetables as well as ornamental plants. Six different accessions of Amaranth from different geographic locations in Indiawere procured from National Bureau of Plant Genetic Resource, New Delhi in the year 2011. In this present study, the genetic diversity and phylogenetic relationships among six accessions of Amaranthus sp were studied using RAPD molecular marker technique. RAPD analyses have been carried out by using four arbitrary decamer primers. On the basis of RAPD data, accession IC 95609, IC 35482 and IC 95595 were very close to each other as they share the same geographical region. Accessions IC 95609 and IC 35482 showed highest similarity (86%). Accession no. IC 120617 is close to accession no. IC 35626 as those accessions originated from Gujrat.